Comparing the Diagnostic Performance of [18F]PSMA‐1007 With [68Ga]Ga‐PSMA‐11 in PET/CT Imaging and Staging of Recurrent Prostate Cancer - Negar Abdi; Miad Alsulami; Hamid Ghaznavi (Medicine Advances)
ABSTRACT PET/CT has become the reference standard imaging modality for diagnosing prostate cancer because of its ability to target prostate‐specific membrane antigen (PSMA), a protein specific to prostate cells. [68Ga]Ga‐PSMA‐11 was a major advance, but limitations such as a short lifespan and image blurring led to the introduction of [18F]PSMA‐1007, which offers advantages such as a longer lifespan and clearer images. This study aimed to compare the effectiveness of [18F]PSMA‐1007 and [68Ga]Ga‐PSMA‐11 in the detection and staging of recurrent prostate cancer because there is currently insufficient evidence to conclude that one PSMA‐radiotracer is better than the other. Both 68Ga and 18F‐labeled PSMA‐radiotracers have similar detection rates in patients. Therefore, more investigation is required to authoritatively conclude which radiotracer results in optimal performance for diagnosing prostate cancer lesions on PET/CT. In this narrative review, we focus on comparing the effectiveness of [18F]PSMA‐1007 with that of [68Ga]Ga‐PSMA‐11 in the detection of recurrent prostate cancer and determination of its stage. We found that [18F]PSMA‐1007 and [68Ga]Ga‐PSMA‐11 showed similar diagnostic performance, with [18F]PSMA‐1007 having slightly higher sensitivity for primary and metastatic recurrent prostate cancer. However, a lack of statistical significance in the differences between the two radiotracers indicates comparable diagnostic accuracy, enabling their interchangeable use based on availability and cost efficiency.